Usefulness of Chest Ultrasonography in Predicting Diagnosis in Non-emergency Small Animal Patients With Lung Parenchymal and Pleural Disease - Lin, Chung-Hui; Lo, Pei-Ying; Lam, Man-Cham; Wu, Huey-Dong (Frontiers in Veterinary Science, 2020)
Chest ultrasonography has become an indispensable tool for pulmonary specialists in human medicine, but its current use in dogs and cats is primarily for emergency. The diagnostic performances of various ultrasonographic features other than comet-tail artifacts are of limited information in veterinary literatures. Therefore, the aims of this retrospective study were to investigate ultrasonographic findings in feline and canine respiratory patients with lung parenchymal and pleural space diseases, and to assess how ultrasonographic features correspond to specific diagnoses. Sixty-five non-emergency cases with radiographically identified lung parenchymal and pleural space abnormalities were included. Medical records and ultrasound video clips were reviewed, and additional follow-up information was subsequently collected. Common findings such as comet-tail artifacts (87.7% of cases), consolidation (84.6%), and thickened/irregular pleura (69.2%) were not distinguishable for a specific diagnosis. The presence of nodular/mass-like lesion (OR=212, p<0.001) and consolidated lesion with heteroechogenicity (OR=240, p<0.001) was significantly associated with and strongly predictive of neoplasia after age, body weight and other sonographic findings were adjusted. The finding of nodular/mass-like lesion has the best diagnostic performance (AUC=0.93) for neoplasia, with sensitivity of 91.7% and specificity of 93.6%. For predicting a diagnosis of pneumonia, although several sonographic features were found to be statistically associated with pneumonia, only a negative finding of nodular/mass-like lesion showed good diagnostic performance (AUC=0.83, sensitivity 95.7%, specificity 71%). These findings demonstrate the value of chest ultrasonography in predicting diagnosis in non-emergency cases. The application of thoracic ultrasound in small animal respiratory patients as part of non-invasive assessment warrants further investigation.